Transcendental Communication in the Wae Rebo Traditional Ritual: A Study of Harmony between Local Values and Religiosity - Hidayatullah, Sarif (The Future of Education Journal, 2025)
This study examines transcendental communication in the Wae Rebo traditional ritual, aiming to analyze how such practices create harmony between local cultural values and modern religiosity. The research employed a qualitative communication ethnography design, utilizing participant observation, in-depth interviews with traditional and religious leaders, and visual and textual documentation. Data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The research population comprised the Wae Rebo community, with a purposive sample of 7–10 informants involved in the core rituals. The findings reveal that transcendental communication is manifested through sacred prayers, symbolic offerings, ritual music and dance, and the sacred space of Mbaru Niang as a symbolic connector between humans, ancestors, and the spiritual realm. In conclusion, the Wae Rebo community successfully integrates ancestral traditions with Catholic religiosity, thereby strengthening cultural identity and social cohesion. This study provides new insights into transcendental communication as an integrative bridge between culture and spirituality.